The Psycholinguistic Theories in the Muqaddimah of Ibn Khaldūn - Abdussalam, Ahmad Shehu (Intellectual discourse, 1995)
A review of psycholinguistic theories found in the Muqaddimah shows the breadth of Ibn Khaldūn's understanding of human behaviour, including language behaviour. His views on the influence of change on human habits, the relationship between language, knowledge and perception, and on the influence of constant repetition on language acquisition are, with minor modifications, valid even in the contemporary period. The causes he described for language corruption and the limitation of non-Arabs in learning Arabic are still worth examining.